Analisis Pengaruh Penetapan Harga Jual Produk Terhadap Volume Penjualan Produk Hortikultura Organik Di Kebun Praktek Fakultas Teknologi Pangan, Pertanian Dan Perikanan Universitas Nusa Nipa - Maria Aspina Gelu; Sarlina Noni; Yoseph Yakob Da Rato (Jurnal Ilmiah Wahana Pendidikan, 2023)
Sales volume is the final result achieved by the company from the results of selling products produced by the company. Product selling price determination requires various considerations that are integrated through production costs, operational costs, desired profit targets, people's purchasing power, competitors' selling prices. The determination of the selling price of the product must be a policy that must be thoroughly considered and integrated. The research was conducted in agricultural practice gardens from August 15 – December 17, 2022. The purpose of the study: to find out: to determine the Effect of Product Selling Price Determination on the Sales Volume of Organic Horticultural Products in the Practice Garden of the Faculty of Food Technology, Agriculture and Fisheries, Nusa Nipa University. The analysis method used is a qualitative method, using questionnaires and statistical tests, namely: validity test, reability test, normality test and then this data is processed using parametic statistics of correlation and simple linear regression. Based on the results of statistical test calculations, an adjusted R Square regression value of 0.174 was obtained. This suggests that variable: pricing has a positive and significant effect on sales volume which can be explained by the R value of 17.4%. The R square value obtained is a small number, meaning that the effect of the Selling Price on Sales Volume is relatively weak